Sistem Informasi Pembelajaran Online Pada SMK PGRI 1 Jakarta - Endah Wiji Lestari; Nurfitri Yani (Paradigma, 2019)
SMK PGRI 1 JAKARTA is an educational institution that is on the road PLK II no.25 East Jakarta. Learning system that occurs in SMK PGRI 1 JAKARTA is still done in a conventional way, which the teachers and students do the teaching and learning process with face to face in a classroom. Conventional learning system, the teacher is unable to attend with a goal or time that is not sufficient in the delivery of subjects. Then there will be ineffectiveness of teaching and learning process. With the identification of problems above, it can be concluded that SMK PGRI 1 requires an online-based learning media that can help teachers and students in the effectiveness of learning in SMK PGRI 1. Research methods used in this paper is the technique of data writing and system development model. Problems that exist in SMK PGRI 1 Jakarta among them is the absence of online learning media, teaching methods are still done directly in the classroom, Limited time of study in class so that materials that require discussion in a long time should be explained in a short time and if the teacher unable to attend for a reason it will result in delayed delivery of material that has been adjusted based on the curriculum, Lack of efficiency and practicality for students in obtaining material or collecting tasks. Because there are still many teachers in providing materials and gathering tasks conventionally or manually, so that felt inefficient in time and energy.